2009
DOI: 10.1021/jo802797e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Oligo[n]cruciforms: Nanosized Sterically Encumbered Tetraethynylphenyl-Homologated Fluorophores

Abstract: A series of nanosized phenyleneethynylenes have been prepared which are sterically insulated from the surrounding environment by multiple functionalization with triisopropylsilyl (TIPS) substituents. The phenyleneethynylenes comprise oligo[n]cruciforms 1-4 (n = 3-5) and a dehydrotribenzo[12]annulene 5, the former of which possess para-acyclic and the latter ortho-cyclic electronic conjugation pathways. All compounds were characterized by (1)H and (13)C NMR, IR, and mass spectroscopic techniques. The X-ray crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 96 publications
3
27
0
Order By: Relevance
“…[58] Further studies have since been reported for [12]DBAs functionalized with CN, F, and COOMe acceptor, and NR 2 and OMe donor groups, [42,47] and [12]DBAs variously functionalized with ethynyl substituents. [13,59] In accordance with the conclusions from theoretical studies, [42] acceptor substituents facilitate reduction of the [12]DBA ring system relative to 1, while donor functionality enables oxidation processes to occur. Ethynyl substituents stabilize the [12]DBA ring to reduction relative to 1.…”
Section: Electrochemical Study Ofsupporting
confidence: 77%
“…[58] Further studies have since been reported for [12]DBAs functionalized with CN, F, and COOMe acceptor, and NR 2 and OMe donor groups, [42,47] and [12]DBAs variously functionalized with ethynyl substituents. [13,59] In accordance with the conclusions from theoretical studies, [42] acceptor substituents facilitate reduction of the [12]DBA ring system relative to 1, while donor functionality enables oxidation processes to occur. Ethynyl substituents stabilize the [12]DBA ring to reduction relative to 1.…”
Section: Electrochemical Study Ofsupporting
confidence: 77%
“…11 Arylalkynes are known to serve as intriguing building blocks for the covalent construction of molecular architectures. [12][13][14][15][16] The viability of interparticle linkages via coordination of the methylthio groups of V-, Y-, and X-shaped arylethynes to gold surfaces was demonstrated recently in our laboratory. 17, 18 However, a key challenge is to determine the interparticle properties of such interparticle assemblies mediated by shaped methylthio arylethynes (MTAs) for exploiting their unique optical and electrical properties.…”
Section: Introductionmentioning
confidence: 93%
“…Subsequent de-silylation of 10 with [(nBu) 4 N]F in THF/H 2 O yielded 11, which was isolated in 91 % yield after workup. A further Sonogashira reaction of 11 and two equivalents of 12 [43] mediated by [PdCl 2 A C H T U N G T R E N N U N G (PPh 3 ) 2 ] and CuI as catalysts afforded 13 in 41 % yield. Longer reaction times facilitated higher yields of 13, although the overall moderate yields of the latter terpyridine were ascribed to extensive byproduct contamination.…”
Section: Resultsmentioning
confidence: 99%